EKSPLORASI BULAN SEBAGAI AYAT KAUNIYAH DALAM TAFSIR AL-QUR'AN - Umar Zakka; Hosen; Sawaluddin Siregar; Nosudera TTR (Yayasan Baitul Hikmah al-Zain, 2025)
This article examines the moon as one of the kauniyah verses in the Qur'an. These verses are signs of Allah's greatness found in the natural world. The moon is understood not only as the Earth's natural satellite, but also as holding significant theological and scientific meaning in Islam. Using a qualitative approach based on a literature review, this study explores the harmony between Qur'anic descriptions of the moon and modern scientific findings. These findings include its orbital movement, role in ocean tides, and contribution to climate stability. The findings demonstrate that Qur'anic verses about the moon strengthen belief in Allah's power and encourage Muslims to view scientific inquiry as a form of worship. The moon plays an important role in timekeeping, particularly in the determination of the Hijri calendar and Islamic rituals. Understanding the theological and scientific aspects of the moon invites Muslims to reflect more deeply on the divine order of the universe. This study emphasizes the importance of integrating Qur'anic interpretation with scientific knowledge to strengthen faith and inspire scientific curiosity within the Muslim community.